New and Rare Spider Species (Arachnida, Araneae) from Ukraine - Polchaninova, N.; Gnelitsa, V.; Terekhova, V.; Iosypchuk , A. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2021)
An annotated checklist of 31 spider species belonging to 12 families is presented. The material was collected recently in Northeast, East and South Ukraine. Marinarozelotes manychensis (Ponomarev & Tsvetkov, 2006), Turkоzelotes mirandus Ponomarev, 2011, Zelotes atrocaeruleus (Simon, 1878), Z. puritanus Chamberlin, 1922, and Heriaeus horridus Tyschchenko, 1965 are recorded from Ukraine for the first time. For Micaria coarctata (Lucas, 1846), it is the first record from the East European Plain. Ten species are new to Left-Bank Ukraine. To date, 1079 species have been recorded from Ukraine and 756 species from Left-Bank Ukraine. According to recent data, the northern boundaries of the geographic ranges of Drassyllus crimeaensis Kovblyuk, 2003 and Bassanioides caperatus (Simon, 1875) run along the northern coast of the Sea of Azov. For Marinarozelotes manychensis, Turkоzelotes mirandus, and Heriaeus horridus, the coastal area of Zaporizhzhia Region is the westernmost known limits of their distiribution. Thirteen species are illlustrted.